Developing big data capabilities in developing countries: Evidence from a cross industry study in Ghana - John Serbe Marfo; Richard Boateng (International Telecommunications Society (ITS), 2015)
Big data is a phenomenon which is generating a lot of interest in academia and practice. In the mist of all this excitement lies a world of uncertainty that most firms seem not to be able understand, how to develop, deploy or combine the capabilities of big data to obtain the benefits that big data offers. To address this, this research uses dynamic capabilities as its theoretical lens to bring clarity to this problem. The research establishes 6 broad categories which makes up the typology of big data capabilities. The big data capabilities identified are technological, data management, legal and ethical, analytical, data sharing and decision making capabilities. The research further establishes the benefit dimensions of big data as organizational, managerial, strategic, IT infrastructure and operational benefits. Using the component factors of dynamic capabilities namely adaptive, absorptive and innovative capabilities, as well as the individual, routine/processes, organization and industry levels of analysis of dynamic capabilities, the research establishes a big data capability conceptual model which is currently being tested for understanding and possible modification with empirical data. The empirical data is being gathered from a cross industry perspective with the sector industries being healthcare insurance, banking and telecommunication.
Keywords: 330; Big data; big data capabilities; big data benefits; dynamic capabilities